Deciphering the puzzle: a case report of Tjalma syndrome (pseudo-pseudo Meigs' syndrome) with profoundly elevated CA-125 and pleural effusion - Tan, Qing; Xu, Li Feng; Yan, Ting; Huang, Cheng Hui; Tao, Yi; Huang, Wen Hui; Yu, Shui Lian (Frontiers in Immunology, 2023)
Elevated CA-125 levels, polyserous effusions (such as pleural effusion, ascites, etc.) in young women with systemic lupus erythematosus (SLE) may signal pseudo-pseudo Meigs' syndrome (PPMS), after excluding other causes. We describe a 32-year-old SLE patient with recurrent bilateral pleural effusions and unexplained hypercalcemia for 10 months. Extensive evaluations revealed no infections or tumors. Cytokine analysis showed elevated interleukin (IL) levels, especially IL-6 in pleural effusion. Treatment with immunosuppressive therapy resulted in reduced cancer antigen (CA) 125 levels and decreased effusion volume, demonstrating a positive response to intervention in this case of PPMS.